Maine’s Public Interest Groups: The Natural Resources Council of Maine - Staff, Editorial (Maine Policy Review, 1993)
The actors in public policy include not only elected and appointed public officials, but also the public interest groups that promote various agendas. To help understand the perspectives of some of these groups, Maine Policy Review continues its profile of Maine's public interest groups in each issue, featuring in this article the Natural Resources Council of Maine.
Keywords: Natural Resources Council of Maine